Prevalence of malnutrition in admitted children and post-intervention parental awareness at a tertiary care hospital - Maju, Archana; Laishram, Rita; Joseph, Riya Mariatte; Sasidharan, Jatheesh Kattuvettiyil; Viswambharan, Anu Reshma (International Journal of Contemporary Pediatrics, 2025)
Malnutrition is a major contributor to childhood morbidity and mortality in India, particularly among hospitalized children who are vulnerable due to underlying illnesses. Parental education has the potential to reduce malnutrition through improved awareness and feeding practices. Objectives were to assess the prevalence of malnutrition among pediatric inpatients and to evaluate the effectiveness of a structured parental education session on caregiver knowledge regarding malnutrition prevention and feeding during illness. A cross-sectional pre-post educational intervention study was conducted among 20 children (6 months-12 years) admitted to a tertiary care hospital in New Delhi, along with their caregivers. Nutritional status was assessed using anthropometric indices and MUAC, based on WHO standards. Caregiver knowledge was assessed using a structured questionnaire before and after a 20-minute education session. Data were analysed using descriptive statistics and paired t-test. The prevalence of malnutrition was high, with 70% of children classified as malnourished. Specifically, 35% had grade I, 20% grade II, and 15% grade III malnutrition, while MUAC assessment revealed 30% severe and 40% moderate malnutrition. Chronic illnesses such as kidney disorders and cancer were commonly associated. The mean caregiver knowledge score improved significantly from 13.3 (pre-test) to 21.0 (post-test), with a mean difference of 7.7 (t=-17.5, p<0.05). Malnutrition was highly prevalent among hospitalized children. A brief structured parental education session significantly improved caregiver knowledge, underscoring the importance of integrating parental counselling into routine pediatric ward care to address malnutrition.